The Effect of Genius Learning Strategy in Enhancing the Students’ Vocabulary Mastery - Hidayah, Taufik; Giffari, Wildana (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2024)
This current study was focused on the effect of genius learning in enhancing students’ vocabulary mastery. the researcher applied Genius Learning Strategy as an alternative way for teaching vocabulary to the students. The strategy emphasized on how to conduct an effective and efficient way of teaching vocabulary. It consisted of 8 steps, namely condusive atmosphere, connect, big picture, determining purpose, information input, activation, demonstration, and review. In this study, the pre-test and post-test were given to both experimental group and control group. Then, the result of both tests was used as the data to be analyzed in this research. The research data was taken from the test and it was analyzed by using t-test formula. Based on the analysis of t-test formula, the result was 8.58 for the value of vocabulary mastery. After it was correlated to the degree of freedom of 78 which was 1.99 from t-table, it is found that the result of t-test is bigger than t-table (8.58 >1.99). Thus, it can be concluded that Genius Learning gave a significant effect in promoting students’ vocabulary mastery